Obedu Festival: Foregrounding continuity, ethics and environmental protection in Yorùbá celebratory art (Namibian Journal of Linguistics, Literature and Communication Studies, 2026)
Festival as an art form is a significant component of people’s cultural trajectory. Among Yorùbá, it recreates age-long traits of the people recognising and transmitting knowledge about a past that impacts the present and also foregrounds the future. Commemorative arts subsist in all cultures of the world articulating the socio-historical imaginaries of the people alongside their biological forms of identity. Although there are existing works on Yoruba festivals mainly focusing on festivals of big cities such as Osun (Osogbo), Eyo (Lagos), and Olojo (Ile-Ife). However, it is imperative to research the festivals of the smaller villages and communities because of their rich history and tradition. Therefore, this paper examines the Obedu festival of the Oba-Ile people of Osun State, Nigeria. Symbolic Interactionism serves as the theoretical framework and it is ethnographic in design. Data were collected through key Informant Interviews (comprising of the king of Oba-Ile, three high chiefs, and ten other participants at the festival) and Participant observation. Data collected were content analysed. The paper concludes that there is a need to reevaluate Indigenous performance as they continue to influence identity construction and social change despite modernity.
Keywords: Obedu festival; Oba-Ile; identity construction; social continuity; environmental protection